Development of the model to examine the impact of infrastructure on economic growth and convergence - Mačiulytė-Šniukienė, Alma; Butkus, Mindaugas; Davidavičienė, Vida (Journal of Business Economics and Management, 2022)
Core infrastructure, which covers transportation, information and communication (ICT), energy, water and sanitation systems, plays a significant role in economic growth. The development of core infrastructure – one of the European Union (EU) Cohesion Policy (CP) priorities – is heavily funded. However, it remains unclear whether these investments achieve the main aim, i.e. contribute to economic growth and convergence between EU countries and especially regions. A theoretical model addressing the identified issues is needed to assess the impact of infrastructure on economic growth and convergence comprehensively and as accurately as possible. To reach this aim, first, we have disclosed the definition of infrastructure and its structure. Also, we discussed different approaches to the relationship between infrastructure and economic growth. We developed a theoretical model for evaluating infrastructure impact on economic growth and convergence. Moreover, based on the neoclassical approach, we specified an econometric model that includes indicators of different types of infrastructure and assessed growth and convergence outcomes of infrastructure development. Even though we find that infrastructure positively affects growth and convergence, the estimated impact is not statistically significant except for some types of ICT and transport infrastructure.